Differentiation of Human Induced Pluripotent Stem Cells into Keratinocytes. Issue 4 (5th April 2022) - Koch, Peter J.; Webb, Saiphone; Gugger, Jessica A.; Salois, Maddison N.; Koster, Maranke I.
Abstract: Investigating basic biological mechanisms underlying human diseases relies on the availability of sufficient quantities of patient cells. As most primary somatic cells have a limited lifespan, obtaining sufficient material for biological studies has been a challenge. The development of induced pluripotent stem cell (iPSC) technology has been a game changer, especially in the field of rare genetic disorders. iPSC are essentially immortal, can be stored indefinitely, and can thus be used to generate defined somatic cells in unlimited quantities. Further, the availability of genome editing technologies, such as CRISPR/CAS, has provided us with the opportunity to create "designer" iPSC lines with defined genetic characteristics. A major advancement in biological research stems from the development of methods to direct iPSC differentiation into defined cell types. In this article, we provide the basic protocol for the generation of human iPSC‐derived keratinocytes (iPSC‐K). These cells have the characteristics of basal epidermal keratinocytes and represent a tool for the investigation of normal epidermal biology, as well as genetic and acquired skin disorders. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol : Directed differentiation of human iPSC into keratinocytes Support Protocol 1 : Coating cell culture dishes or plates with Vitronectin XF ™ Support Protocol 2 : Freezing iPSC Support Protocol 3 : Preparing AggreWell ™ 400 6‐well plates for EB formation Support Protocol 4 : Coating cell culture dishes or plates with Collagen IV Support Protocol 5 : Immunofluorescence staining of cells